2022
DOI: 10.1038/s41598-021-03940-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation (tDCS) reduces motivation to drink ethanol and reacquisition of ethanol self-administration in female mice

Abstract: Transcranial direct current stimulation (tDCS) is an emerging noninvasive brain neuromodulation technique aimed at relieving symptoms associated with psychiatric disorders, including addiction. The goal of the present study was to better identify which phase of alcohol-related behavior (hedonic effect, behavioral sensitization, self-administration, or motivation to obtain the drug) might be modulated by repeated anodal tDCS over the frontal cortex (0.2 mA, 20 min, twice a day for 5 consecutive days), using fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…A constant current of 0.2 mA was applied transcranially in two sessions of 20 min per day for five consecutive days, with a linear fade-in and fade-out of 10 s, using a direct current stimulator (DC-Stimulator Plus) or an Open-tES stimulator (d) [31]. Adapted from Pedron et al (2022) [32].…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations
“…A constant current of 0.2 mA was applied transcranially in two sessions of 20 min per day for five consecutive days, with a linear fade-in and fade-out of 10 s, using a direct current stimulator (DC-Stimulator Plus) or an Open-tES stimulator (d) [31]. Adapted from Pedron et al (2022) [32].…”
Section: Animalsmentioning
confidence: 99%
“…One week before starting the stimulation protocol, a tubular plastic electrode holder (internal diameter 2.1 mm; DIXI Medical, Besançon, France; Figure 5C) was surgically affixed to each mouse's skull, as previously described [27][28][29][30][31][32]. Briefly, the animals were anesthetized with ketamine hydrochloride/xylazine (80/12 mg/kg, intraperitoneal [i.p.]…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical and clinical studies suggest DLPFC stimulation is a promising intervention target for neuromodulation trials in substance use disorder. Preclinical research has reported reduced motivation to consume alcohol, reduced alcohol consumption and reduced reacquisition of ethanol consumption after multiple sessions of transcranial direct current stimulation (tDCS) to the frontal cortex in murine models [17,18]. Clinical studies have reported reduced craving and risk of relapse after multiple sessions (five [2,3] or ten sessions [19]) of DLPFC stimulation.…”
Section: Introductionmentioning
confidence: 99%